Kompetensi Digital Untuk Pengembangan Profesi Guru: Sebuah Kajian Pustaka Terstruktur (A Systematic Literature Review) - Fajar Gumilang Kosasih; siti nurjannah (Economy Deposit Journal (E-DJ), 2022)
This essay offers a thorough analysis of the literature on teachers' professional development and digital competence. Finding current research patterns and making improvements for upcoming research are the goals of this study. The PRISMA Statement Guidelines for Systematic Review and Meta-analysis method is the foundation for the approach adopted. Following the application of inclusion, exclusion, and theme criteria, 25 papers made up the sample for this study. The studies that were chosen stress the significance of digital competence as one of the difficulties that qualitative techniques present for teachers nowadays. This study concludes that the majority of the studies that were chosen showed a lack of teacher preparation and insufficient Information and Communication Technology (ICT) training.